bahasa inggris - Astry Gooniartin (ELATICS JOURNAL, 2025)
This research aims to identify the types of figurative language as well as the denotative and connotative meanings in the lyrics of Niki's song "Blue Moon," released in June 2024. The song portrays a complex emotional journey about a past relationship. This qualitative descriptive study aims to explain and provide a detailed description of the types of figurative language and the meanings within the song, using Abrams' theory of figurative language and Keraf's theory of meaning. The researcher found 22 lines in the song that can be categorized into figurative language, including metaphor, hyperbole, oxymoron, simile, paradox, and understatement. Most of the figurative language used in the song is metaphor, contributing to the beautiful and emotionally charged lyrics of "Blue Moon" by Niki.